Mace-like hierarchical MoS2/NiCo2S4 composites supported by carbon fiber paper: An efficient electrocatalyst for the hydrogen evolution reaction - Sun, Lan; Wang, Tao; Zhang, Long; Sun, Yunjin; Xu, Kewei; Dai, Zhengfei; Ma, Fei (Journal of power sources, 2018)
The rational design and preparation of earth-abundant, stable and efficient electrocatalysts for hydrogen production is currently the subject in extensive scientific and technological researches toward the future of a clean-energy society. Herein, a mace-like MoS2/NiCo2S4 hierarchical structure is designed and synthesized on carbon fiber paper via a facile hydrothermal method, and evaluated as electrocatalyst for hydrogen evolution reaction. In the MoS2/NiCo2S4/carbon fiber paper hierarchical structures, MoS2 nanosheets are dispersively distributed on the surface of NiCo2S4 nanowires, which provides an enlarged surface area, abundant interfaces and catalytic active sites. As for hydrogen evolution reaction, such MoS2/NiCo2S4/carbon fiber paper heterostructures give rise to a hydrogen evolution reaction catalytic current density of 10 mA cm−2 with a lower overpotential of 139 mV and a smaller Tafel slope of 37 mV·dec−1 than those of MoS2/carbon fiber paper and NiCo2S4/carbon fiber paper counterparts, exhibiting a prominent electrocatalytic performance. Moreover, the electrocatalytic properties change little after 5000 CV cycles and continual electrolysis for 12 h without obvious decay, respectively, demonstrating high durability and stability. The excellent hydrogen evolution reaction performances endow the hierarchical configuration MoS2/NiCo2S4/carbon fiber paper with promising alternative in HER and other related renewable energy fields. •A mace-like MoS2/NiCo2S4/CFP structure is facilely fabricated.•Highly dispersed MoS2 nanosheets are formed on NiCo2S4 nanoarrays.•Bimetallic NiCo2S4 nanoarrays modifies the electron transfer characteristics.•The composites exhibit excellent water splitting activity and superior stability.